2011
DOI: 10.1152/ajpheart.00547.2009
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential A1 channel contributes to activation of the muscle reflex

Abstract: Koba S, Hayes SG, Sinoway LI. Transient receptor potential A1 channel contributes to activation of the muscle reflex. Am J Physiol Heart Circ Physiol 300: H201-H213, 2011. First published November 12, 2010; doi:10.1152/ajpheart.00547.2009.-This study was undertaken to elucidate the role played by transient receptor potential A1 channels (TRPA1) in activating the muscle reflex, a sympathoexcitatory drive originating in contracting muscle. First, we tested the hypothesis that stimulation of the TRPA1 located on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…Mechanosensors within the muscle are responsive to muscle force, initiating afferent nerve traffic to the brain, predominantly via group III nerves (477), in a manner proportional to the force developed (864). On the other hand, metaboreceptors within the muscle initiate afferent input primarily via group IV nerves and are responsive a wide variety of factors (e.g., lactate, H + , ATP, ROS, bradykinin, capsaicin) via a variety of receptors and sensitive membrane channels (494, 496, 858, 980). Interestingly, the intensity of neural activation depends upon the type of muscle fiber contracting.…”
Section: Cardiovascular Control In Patients With Peripheral Arterialmentioning
confidence: 99%
“…Mechanosensors within the muscle are responsive to muscle force, initiating afferent nerve traffic to the brain, predominantly via group III nerves (477), in a manner proportional to the force developed (864). On the other hand, metaboreceptors within the muscle initiate afferent input primarily via group IV nerves and are responsive a wide variety of factors (e.g., lactate, H + , ATP, ROS, bradykinin, capsaicin) via a variety of receptors and sensitive membrane channels (494, 496, 858, 980). Interestingly, the intensity of neural activation depends upon the type of muscle fiber contracting.…”
Section: Cardiovascular Control In Patients With Peripheral Arterialmentioning
confidence: 99%
“…One was 30-s continuous static contraction, commonly used to study the physiological roles of the exercise pressor reflex (19,20,37,38,43). Another was 1-min intermittent (1-4 s of stimulation to relaxation) static contraction.…”
Section: H148mentioning
confidence: 99%
“…A prior study has demonstrated that intra-arterial injection of AITC, a TRPA1 agonist, into the hindlimb muscle circulation of healthy rats led to increases in SNA and BP via a reflex mechanism [28]. Also, this study has suggested that TRPA1 plays a role in regulating the metabolic component of the exercise pressor reflex.…”
Section: Introductionmentioning
confidence: 68%